Security analysis techniques using differential relationships for block ciphers - Buja, Alya Geogiana (2018)
The uses of block cipher has become crucial in nowadays’ computing era as well as the information security. Information must be available only for authenticated and authorized users.However,flaws and weaknesses in the cryptosystem can breach the security of stored and transmitted information.A weak key in the key schedule is well-known issues which may affect several round keys have same bits in common.Besides,information leaked from the implementation also affects the security of block ciphers.Based on the flaws and leakage,the adversary is able to assess the differential relationships in block cipher using differential cryptanalysis technique. Firstly,the existing differential cryptanalysis techniques have been evaluated.Secondly,based on the gaps that have to be filled in the existing differential cryptanalysis techniques,new frameworks of differential cryptanalysis techniques have been proposed and designed by using Pearson correlation coefficient,Hamming-weight leakage assumption and reference point.The Pearson correlation coefficient is used to determine the repeated differential properties in the key schedules.Meanwhile, reference point and Hamming-weight leakage assumption are used to assess the security of the implementation of block ciphers against side-channel cube attack and differential fault analysis.Thirdly,all proposed frameworks have been assessed.The results show that the repeated differential properties are found for AES, PRESENT and Simeck key schedules.However,AES key schedule is definitely ideal to be adopted in the design for the future cryptographic algorithm.In addition,the newly designed frameworks for side-channel differential analysis techniques have been able to reduce the attack complexities for Simeck32/64,KATAN32 and KTANTAN32 compared to previous work.In conclusion,the proposed frameworks are effective in analyzing the security of block ciphers using differential cryptanalysis techniques.